Wireless Control of Modular Multilevel Converter Submodules - Ciftci, Bars; Schiessl, Sebastian; Gross, James; Harnefors, Lennart; Norrga, Staffan; Nee, Hans-Peter (IEEE transactions on power electronics, 2021)
Wireless control of modular multilevel converter (MMC) submodules offers several potential benefits to exploit, such as decreased converter costs and ease in converter installation. However, wireless control comes with several challenging engineering requirements. The control methods used with wired communication networks are not directly applicable to the wireless control due to the latency and reliability differences of wired and wireless networks. This article reviews the existing control architectures of MMCs and proposes a control and communication method for wireless submodule control. Also, a synchronization method for pulsewidth modulation carriers is proposed suitable for wireless control. The imperfections of wireless communication, such as higher latency and packet losses compared to wired communication, are analyzed for the operation of MMCs. The latency is fixed with a proper controller and wireless network design. The converter is rendered immune to the packet losses by decreasing the closed-loop control bandwidth. The functionality of the proposal is verified, for the first time, experimentally on a laboratory-scale MMC using a simple wireless network. It is shown that wireless control of MMC submodules with the proposed approach can perform comparably to the wired control.